Problematik Analisis Ekonomi Terhadap Hukum Tindak Pidana Pencucian Uang - Ade Riyanda Prasetia Putra (Universitas Islam Indonesia, 2019)
Prevention and eradication of money laundering in Indonesia began on 17 April 2002 with the enactment of Law No. 15 of 2002 on Criminal Acts of Money Laundering. In fact, the stages of preventing money laundering were carried out before the law was enacted, but the scope was limited to banks. The purpose of this study is to analyze how is the law enforcement against economic violations in money laundering. The method used is the study of literature from libraries and the internet. The results of the study show that the enforcement of money laundering law or anti-money laundering regime is different from conventional criminal law enforcement. Disclosure of criminal acts and perpetrators of money laundering crimes is more referring to tracing the flow so it is not apparent that the funds originate from acts of illicit funds / money. At present, the eradication of money laundering in Indonesia is regulated in Law No. 8 of 2010 on Prevention and Eradication Criminal Acts of Money Laundering (Law 8/2010). Law No. 8 of 2010 replaces the previous law governing money laundering, namely Law No. 15 of 2002 as amended by Law No. 25 of 2003. Sanctions of money laundering in the form of imprisonment for a minimum of 5 years and a maximum of 15 years and a minimum fine of Rp. 5,000,000,000.00 and a maximum of Rp. 15,000,000,000.00